One-pot, ligand-free, room-temperature synthesis of Au/Pd/ZnO nanoclusters with ultra-low noble metal loading and synergistically improved photocatalytic performances. Issue 37 (28th June 2021) - Wei, Yunwei; Shahid, Malik Zeeshan; Lyu, Shujuan; Sun, Weiying; Lyu, Shuqiang
Abstract : Au/Pd/ZnO nanoclusters with ultra-low noble metal loadings were prepared by a one-step and ligand-free method at room temperature. The obtained Au/Pd/ZnO nanoclusters were composed of ZnO nanoclusters decorated with well-dispersed AuPd NPs with ultra-low noble metal loading. Abstract : Au/Pd/ZnO nanoclusters with ultra-low noble metal loadings were prepared by a one-step and ligand-free method at room temperature. HRTEM, ICP-MS, XPS, and elemental mapping analysis confirmed that the obtained Au/Pd/ZnO nanoclusters were composed of ZnO nanoclusters decorated with well-dispersed AuPd nanoparticles. Au/Pd/ZnO nanoclusters exhibited higher photocatalytic activity compared with those of pristine ZnO, Au/ZnO and Pd/ZnO. Moreover, the high catalytic activity of Au/Pd/ZnO nanoclusters could be maintained even after 5 cycles of photocatalytic reaction. A mechanism for the enhanced photocatalytic performance was also suggested, which was in light of the synergistic effects of the SPR effect from Au and the improved photogenerated charge carrier separation from Pd.